(untitled) (LEARNing Landscapes, 2013)
In this interview, Tom Snyder recounts how his technological curiosity led him to build computers at a very young age. He describes how later, as a fifth grade science teacher, he started writing big group simulations on a RadioShack TRS80 computer, which served as the launching point for his future and ongoing career as an educational software developer. He talks about the key changes and trends he has witnessed over the past 40 years in the realms of technology, business, and education. In addition, he critically discusses the works of Vygotsky and Piaget as well as the "huge influence" that Jerome Bruner’s educational path had on his life.